Encyclopedia of Computational Mechanics 2004
DOI: 10.1002/0470091355.ecm061
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Closure Models for Computational Fluid Dynamics

Abstract: The formulation of analytical turbulence closure models for use in computational fluid mechanics is described. The subject of this chapter is the types of models that are used to predict the statistically averaged flow field-commonly known as Reynolds-averaged Navier-Stokes equations (RANS) modeling. A variety of models are reviewed: these include two-equation, eddy viscosity transport, and second moment closures. How they are formulated is not the main theme; it enters the discussion but the models are presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…We can model the turbulent Reynolds stress in terms of the large‐scale flow with the aid of the Reynolds‐averaged Navier‐Stokes (RANS) equations. Following the RANS k ‐ ϵ model (Durbin, 2004), for a homogeneous and stationary turbulent flow in water, we can parameterize the local turbulent Reynolds stress trueuiuj by a turbulent eddy viscosity ν T acting on the large‐scale flow gradients S ij as (Durbin, 2004) trueuiuj+23trueukuk0.1emδij2νTSij. The mean flow strain tensor S ij is given by Sij12()uixj+ujxi. …”
Section: Theoretical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We can model the turbulent Reynolds stress in terms of the large‐scale flow with the aid of the Reynolds‐averaged Navier‐Stokes (RANS) equations. Following the RANS k ‐ ϵ model (Durbin, 2004), for a homogeneous and stationary turbulent flow in water, we can parameterize the local turbulent Reynolds stress trueuiuj by a turbulent eddy viscosity ν T acting on the large‐scale flow gradients S ij as (Durbin, 2004) trueuiuj+23trueukuk0.1emδij2νTSij. The mean flow strain tensor S ij is given by Sij12()uixj+ujxi. …”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…With turbulent production P defined as Ptrueuiuj0.1emSij, then after replacing the Reynolds stress trueuiuj by its ν T parameterization, we obtain a simple estimate of turbulent dissipation in terms of large‐scale flow gradients as (Durbin, 2004) ϵP=2νT()Sij2. …”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Chorin's projection method Chorin (1968) is used for the pressure treatment and a preconditioned BiCGStab solver van der Vorst (1992) is used to solve for the pressure. Turbulence modelling is carried out based on Durbin's modification Durbin (2004) of the two equation k-ω model proposed by Wilcox Wilcox (1994). Eddy viscosity, ν t , is bounded to avoid unphysical overproduction of turbulence in strained flow as shown by DurbinDurbin (2009).…”
Section: Numerical Modelmentioning
confidence: 99%
“…especially Ross and Vosper (2005) and Sogachev et al (2012). Durbin (2004) and Hanjali'c and Kenjereš (2008) provide recent reviews of the strengths and limitations of these models. Interestingly in the light of our discussion of simple canopy flows, Katul et al (2004) found that K-theory models with prescribed mixing lengths in the canopy performed as well as k − ε models in simple canopy flows.…”
Section: Eddy Diffusivities In Complex Canopy Flowsmentioning
confidence: 99%